Inventaires et catalogues, une longue histoire - Annie Berthier (Université de Provence, 2002)
The composition and organisation of the Middle Eastern collection in the National Library of France (BNF) goes back to the 16th century. From the beginning of the 17th century, an interest in literature and scientific knowledge from other countries and cultures is expressed by the acquisition of Middle Eastern books; this acquisition is random at first but then becomes increasingly focused and rigorous. In the Encyclopaedia, D'Alembert cites the study of languages as one of the essential components of knowledge. In the 18* century, Volney considers the question of the transliteration of Middle Eastern languages as well as their typography in the original letters. But the real period of erudition begins at the end of the 18th century and continues into the 19th: in order to study these books, new instruments of analysis are developed such as dictionaries, grammar books and translations. This is also seen in libraries which held works on the Middle East: instead of simply drawing up inventories, increasingly detailed catalogues were written. This reflects a change in the outlook on the world, an outlook which becomes more and more precise and analytic and one which seeks to observe «everything which does not fall under the category of sense», in other words, everything which can be measured and counted.